The Relationship Between Learning Time Management and PKN Learning Outcomes in Class XI of SMK Swasta Harapan Bangsa - Alimin Purba; Chainar Elli Ria; Sondang Ni Bulan Marbun; Khairil Fauzan (STAI Hubbulwathan Duri, 2023)
This study aims to determine the significant relationship between time management and civic learning outcomes for Harapan bangsa Private Vocational High School students during the year. Studies of this type are descriptively correlated. The population of this study consists of all her XI students of SMK Swasta Harapan Bangsa in 2022 and the population of this study is 30 using the whole sample. The tools used for data collection were questionnaires and documents, study time management had 15 items with 4 options tested for validity and reliability, and learning outcomes included document student performance lists. I'm using. Results of normality analysis of timekeeping data test results for Class XI SMK Swasta Harapan Bangsa in 2022 were normally distributed with calculation x2count x2table (7.27 43.77). The civics learning outcomes of students in Class XI of Harapan Bangsa Private College in 2022 are normally distributed with the calculated result x2h x2t (17.11 43.77). Control data linearity test results. Learning time due to civic learning outcomes is linear in the equation Y= 75.62+ 0.03 X, consistent with FcountFtable (28 4.20). 2022 Harapan Bangsa Private College Class XI students' study time management propensity test results are moderate (50%) and 2022 Harapan Bangsa Private College Class XI civics learning outcomes are rather (63.33%). Based on the results of the correlation coefficient analysis test, X and Y got rcount = 1.831 and rtable = 0.349 (1.831 0.349 ). This demonstrates a correlation between learning time management and XI citizenship learning outcomes. SMK Swasta Harapan's class gives Bangsa. If we get tcount = 4.11 and ttable = 1.69 (tcount ttable)(4.11 1.69), and with the